ANALYSIS OF AUTHENTICITY OF TEACHERS’ MADE ASSESSMENT AND ITS CONTRIBUTION TO STUDENTS’ ENGLISH ACHIEVEMENT IN ELEMENTARY SCHOOLS IN BULELENG REGENCY - Natalia, S. A. M. K. D.; Marhaeni, A.A.I.N; Dantes, N. (Universitas Pendidikan Ganesha, 2013)
Abstract This study aimed at analyzing and investigating the authenticity of teacher?s made assessment and its contribution to students? English achievement in Elementary schools in Buleleng regency. The authenticity of teachers? made assessment was seen in terms of teachers? assessment planning, assessment implementation as perceived by teachers, teachers? assessment implementation as perceived by students. This study was also intended in order to know the contribution of those aspects to students? English achievement. The research design for this study was Exploratory Mix-Method design, involving 33 English teachers. The data were collected through documentation, and questionnaires which were analyzed qualitatively and quantitatively. The result of data analysis showed that teachers? assessment planning, assessment implementation as perceived by teachers and students had sufficient level of authenticity. From statistical analysis, it was found that only teachers? assessment planning and assessment implementation as perceived by students which had significant contribution to students? English achievement. However, it was also found that the three aspects were integratedly gave significant contribution to students? English achievement. In conclusion, it showed how the teachers? assessments with its level of authenticity gave contribution to the students? English achievement. Keywords: teachers? assessment authenticity, students? achievement